NEEDS ANALYSIS ON ZOOM MEETING-BASED LEARNING IN ENHANCING ELEMENTARY STUDENTS’ MATHEMATIC COMMUNICATION SKILL - Lathifah, Naili Darojatil; Lestari, Wahyu (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
The purpose of this research is to analyze how video conference application technology via Zoom Meeting can improve students' mathematical communication skills based on the educators’ or teachers’ perspective. The research was conducted using descriptive qualitative methods with an emphasis on needs analysis. The data collection technique was carried out with several instruments including interviews, documentation, questionnaires, and tests related to students' mathematical communication skills given to several students by the help of their respective teachers. The results of this study indicate that 80% of teachers still use assignments as a tool to determine students' mathematical communication skills and 67% of students' mathematical abilities have decreased from before the pandemic period so that a learning model is needed that is in accordance with current educational conditions, especially in improving students' mathematical communication skills. Therefore, the application of the problem-based learning model with a realistic mathematics approach on the Zoom Meeting based learning is expected to improve the communication skills of elementary school students.